Some inequalities for cr-log-h-convex functions - Wei Liu; Fangfang Shi; Guoju Ye; Dafang Zhao (Journal of Inequalities and Applications, 2022)
Abstract The main purpose of this paper is to study certain inequalities for cr-log-h-convex functions with an interval value. To this end, we first give a definition of cr-log-h-convexity of interval-valued functions under the cr-order and study some properties of such functions. On this basis, we establish the Jensen-, Hermite–Hadamard-, and Fejér-type inequalities for cr-log-h-convex functions, and discuss some special cases. In addition, we give some numerical examples to illustrate the accuracy of the results obtained.